Wavelength assignment algorithms for optical multicast in WDM networks - Zhou, Yinzhu (2008)
This PhD thesis provides a comprehensive research on the topic of wavelength assignment algorithms for optical multicast in WDM networks. Several algorithms and schemes are proposed to solve the multicast wavelength assignment problem on different wavelength conversion scenarios in terms of cost issues.